Vidensflow: Hvordan kan forbindelserne mellem forskning og uddannelse i professionshøjskoler begribes? - Jensen, Jens-Ole; Lund, Jens H. (Tidsskrift for Professionsstudier, 2019)
In 2013, the University Colleges in Denmark was legalized as research-based institutions and the nexus between research and education is therefore rather unexplored in the area of universities of applied science. The demand of being research based educations combined with limited research based knowledge of nexus between research and education call upon development of clear concepts. The study show that the arena of education is mainly positioned as recipient in relation to the arena of research and the article argues for a mutual optic on the nexus. In the research literature there is a lack of systematic conceptualization of the different types of connections between the two areas. The article suggests a three-piece typology: a materialized, an actor and an organizational connection.